Potential intermediates for incorporation of polyhydroxylated prolines into combinatorial libraries - Long, D; Frederiksen, S; Marquess, D; Lane, A; Watkin, D; Winkler, D; Fleet, G (1998)
Bicyclic 2 and monocyclic 6 2-amino-1,4-lactones provide divergent intermediates for subsequent incorporation of polyhydroxylated prolines into combinatorial amide libraries. The X-ray crystal structure of an azidolactone, combined with molecular modelling, rationalises the very different behaviour of two azidolactones which are epimeric at a remote side- chain carbon. The conversion of 2 and 6 into DGDP 4 secures the structural claims in the paper. The enantiomers of 2 and 6 may provide access to libraries of potential inhibitors of UDP-Gal mutase and thus of mycobacterial cell wall biosynthesis.